Academic identity formation: the influence of space. Issue 1 (2nd January 2023) - Barrow, Mark; Xu, Linlin
ABSTRACT: This qualitative study explores novice nurse academics' experiences and perceptions of academic identity formation through the theoretical lens of space. We analyse the data from four participants through semi-structured interviews, supplemented with information from demographic questionnaires and career incident maps. Our analysis shows a dual, inter-reliant, tension-filled and on-going process of identity construction – the formation of an academic identity and the reinvention of a clinical identity. This identity construction happens when the nurse academics move back and forth between academic and clinical spaces and is manifested in the emergence of the nurse academic identity. Findings reveal shifts within nursing as a profession and an academic discipline. To conclude, we suggest a contextualised approach to academic identity research to recognise the variability and complexity of academic identities (and spaces) in universities and the need to facilitate clinical engagement in the academic spaces of nursing to foster academic identity formation.